Study on acceptance of Google Meet as a learning platform among students in higher education preliminary / Muhammad Aiman Abdul Halim and Rofiza Aboo Bakar - Abdul Halim, Muhammad Aiman; Aboo Bakar, Rofiza (Universiti Teknologi MARA, Pulau Pinang, 2022)
For nearly two years in the Coronavirus disease (COVID-19) pandemic, many institutions have been using Google Meet as the main teaching platform for online classes. However, not many researchers focus on the use of this platform from students' perspectives (Diaz-Nunez et al., 2021). This research aims to understand students' perspectives of Google Meet as a learning platform in higher education by using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This quantitative study had analyzed 108 responses from students, obtained using purposive sampling. Descriptive statistical (mean, standard deviation) analysis of the collected data was done using DATAtab software. The result suggests that effort expectancy (EE) was seen as the most important factor that influenced their use of Google Meet. On the contrary, performance expectancy (PE) was seen as the least influencing factor by the students. In conclusion, students considered Google Meet as an easy-to-use classroom technology. However, educators should not rely entirely on it during online learning and need to incorporate other additional applications to further improve learning effectiveness.